Seismic swarms and diffuse fracturing within Triassic evaporites fed by deep degassing along the low‐angle Alto Tiberina normal fault (central Apennines, Italy). Issue 1 (5th January 2017) - Piana Agostinetti, Nicola; Giacomuzzi, Genny; Chiarabba, Claudio
Abstract: We present high‐resolution elastic models and relocated seismicity of a very active segment of the Apennines normal faulting system, computed via transdimensional local earthquake tomography (trans‐D LET). Trans‐D LET, a fully nonlinear approach to seismic tomography, robustly constrains high‐velocity anomalies and inversions of P wave velocity, i.e., decreases of V P with depth, without introducing bias due to, e.g., a starting model, and giving the possibility to investigate the relation between fault structure, seismicity, and fluids. Changes in seismicity rate and recurring seismic swarms are frequent in the Apennines extensional belt. Deep fluids, upwelling from the delaminating continental lithosphere, are thought to be responsible for seismicity clustering in the upper crust and lubrication of normal faults during swarms and large earthquakes. We focus on the tectonic role played by the Alto Tiberina low‐angle normal fault (ATF), finding displacements across the fault consistent with long‐term accommodation of deformation. Our results show that recent seismic swarms affecting the area occur within a 3 km thick, high V P / V S, densely cracked, and overpressurized evaporitic layer, composed of dolostones and anhydrites. A persistent low V P, low V P / V S volume, present on top of and along the ATF low‐angle detachment, traces the location of mantle‐derived CO 2, the upward flux of which contributes to cracking within the evaporitic layer. Key Points: High‐resolution local earthquake tomography of a low‐angle normal fault system Correlation between Triassic evaporites, natural CO2 source, and swarm‐like seismicity Seismogenic processes in fault zones, deformation, and tectonics of normal faulting systems